A review of graphene reinforced Cu matrix composites for thermal management of smart electronics - Ali, S. (Elsevier Ltd, 2021)
Heat dissipation remains a key challenge to be addressed, determining the performance and durability of smart electronic devices. Graphene reinforced metal matrix composites have been extensively studied as a thermal management material due to their high thermal conductivity and low coefficient of thermal expansion. The emphasis of this review is pivoted on the thermal conductivity enhancement of graphene reinforced Cu matrix composites developed in the recent literature. An overview of factors affecting thermal conductivity of composite namely defect processing route, density, graphene derivative, lateral size, concentration, alignment, graphene/matrix interfacial bonding and graphene modification are discussed. An extensive weightage is given to the processing route as it is the most influential factor in determining the enhancement efficiency. Furthermore, graphene based functional products such as heat spreader and heat sink developed for heat dissipation of electronic devices are also reviewed. Finally, the development and outlook for graphene based Cu composites are presented. Â© 2021 Elsevier Ltd